Amycolatopsis rhizosphaerae sp. nov., isolated from rice rhizosphere soil - Chitti Thawai (My University, 2018)
A novel actinomycete, designated strain DH51B-4-3T, which formed long chains of spherical spores borne on the tip of sporophores arising from the aerial mycelium, was isolated from rice rhizosphere soil. The isolate contained meso-diaminopimelic acid in the cell-wall peptidoglycan. The whole-cell sugars of strain DH51B-4-3T were arabinose, galactose, glucose, rhamnose and ribose. The phospholipids in the cell membrane were phosphatidylethanolamine, phosphatidyl methylethanolamine, diphosphatidylglycerol and phosphatidylinositol. The major menaquinone was MK-9(H4). The main cellular fatty acids were iso-C16 : 0 and cyclo-C17 : 0. The G+C content of the genomic DNA was 68.2 mol%. Phylogenetic analysis using 16S rRNA gene sequences revealed that strain DH51B-4-3T should be classified in the genus Amycolatopsis and closely related to Amycolatopsis dongchuanensis YIM 75904T (98.06 %) and Amycolatopsis sacchari DSM 44468T (97.77 %). The result of DNA-DNA hybridization and some physiological and biochemical properties indicated that strain DH51B-4-3T could be readily distinguished from its closest phylogenetic relatives. On the basis of these phenotypic and genotypic data, this strain represents a novel species, for which the name Amycolatopsis rhizosphaerae sp. nov. is proposed. The type strain is DH51B-4-3T (=TBRC 6029T=NBRC 112509T).
Keywords: Rhamnose; Arabinose; Strain (injury); genomic DNA; Genomics and Phylogenetic Studies